2017
DOI: 10.1038/s41598-017-10195-3
|View full text |Cite
|
Sign up to set email alerts
|

Key glycolytic branch influences mesocarp oil content in oil palm

Abstract: The fructose-1,6-bisphosphate aldolase catalyzed glycolysis branch that forms dihydroxyacetone phosphate and glyceraldehyde-3-phosphate was identified as a key driver of increased oil synthesis in oil palm and was validated in Saccharomyces cerevisiae. Reduction in triose phosphate isomerase (TPI) activity in a yeast knockdown mutant resulted in 19% increase in lipid content, while yeast strains overexpressing oil palm fructose-1,6-bisphosphate aldolase (EgFBA) and glycerol-3-phosphate dehydrogenase (EgG3PDH) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…Several previous studies in oil palm have shown that high glycolytic activity is associated with high mesocarp oil content ( Loei et al., 2013 ; Wong et al., 2014 ; Wong et al., 2017 ). Similar overexpression of oil palm fructose-1,6-bisphosphate aldolase (FBA) and glyceraldehyde-3-phosphate (G3PDH) resulted in increased lipid content in yeast ( Ruzlan et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several previous studies in oil palm have shown that high glycolytic activity is associated with high mesocarp oil content ( Loei et al., 2013 ; Wong et al., 2014 ; Wong et al., 2017 ). Similar overexpression of oil palm fructose-1,6-bisphosphate aldolase (FBA) and glyceraldehyde-3-phosphate (G3PDH) resulted in increased lipid content in yeast ( Ruzlan et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Glycolysis is a crucial metabolic pathway for supplying precursors for oil biosynthesis [ 45 ]. In various oilseed crops such as Arabidopsis, sunflower, and oil palm, several limiting-rate enzyme genes involved in carbon allocation into oil have been identified to play a critical role in generating precursors for oil biosynthesis and regulating oil accumulation in developing seeds [ 30 , 33 , 46 , 47 , 48 ]. In our analysis, we identified several candidate genes (such as RcGPDH , RcGAPC , RcPGK , and RcPGM ) in glycolysis that may act as limiting-rate enzyme genes for generating precursors of oil biosynthesis in castor-developing seeds.…”
Section: Discussionmentioning
confidence: 99%
“…While the duration of seed development and oil content (TAG content) varied among different cultivars, previous investigations have generally characterized the seed development process of castor beans into three typical stages: the early stage, the rapid oil accumulation stage, and the late stage [17,18]. To characterize the process of oil accumulation during seed development, we divided the seed development of variety ZB306 into three stages, the early (10-20 DAP, days after pollination), middle , and late stage (46)(47)(48)(49)(50)(51)(52)(53)(54)(55), as shown in Figure 1a. Physiologically, in the early stage, there is the down-loading of soluble sugar from capsules where basic carbohydrate metabolism occurs, although the accumulation of TAG does not begin.…”
Section: Dynamics Of Oil Accumulation In Developing Seeds Of Castor B...mentioning
confidence: 99%